OTOMASI KEARSIPAN DI LEGAL OFFICE DI PT. ANGKASA PURA I (PERSERO) CABANG BANDAR UDARA ADISUTJIPTO YOGYAKARTA - , ASTRI WIKANDARI; , Waluyo, S.S., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of technology information provide a positive impact to the world of records. The development of technology information is used as a tool of management of records especially made by paper. It is called the automation of records. The volume of conventional records had been increasing continuously. It makes the Record Manager requires technology to rediscover the record correctly and quickly. The automation of record has been recognized by almost of every office so they use the computers as a basic working tool, that includes PT. Angkasa Pura I. PT. Angkasa Pura I has a branch office in Yogyakarta, it is PT. Angkasa Pura I Adisutjipto International Airport. The company uses the computer and Microsoft Excel to manage the active record in the legal office. The company uses the internet and application called Record Center Information System in the management of inactives record too. The application of records automation is expected to facilitate the management of record more effective and efficient, so that the function of the records can be beneficial as appropriate for the organization.